Balanophora polysaccharide improves renal injury and fibrosis in db/db diabetic nephropathy mice via NLRP3 inflammasome mediated inflammation - Tian, Chaoxi; Ma, Aolong; Song, Tianying; Zhao, Fangyu; Huang, Jing; Gao, Jianhong; Yan, Honglin; Chen, Xianbing (Frontiers in Pharmacology, 2025)
IntroductionDiabetic nephropathy (DN) is a major complication of diabetes, with renal fibrosis leading to progressive renal function decline. Understanding interventions for renal injury and fibrosis in DN is vital, and given its complex pathogenesis, new therapeutic agents are urgently needed.MethodsThe DN model was established using db/db mice, which received balanophora polysaccharide (BPS) treatment. The therapeutic efficacy of BPS for DN was evaluated by measuring body weight, fasting blood glucose (FBG), lipid profiles, renal function parameters, serum inflammatory factors, and histopathological changes. Furthermore, the underlying mechanisms by which BPS exerted its therapeutic effects were investigated using transmission electron microscopy (TEM), immunohistochemistry (IHC), immunofluorescence (IF), and Western blotting.ResultsBPS significantly reduced body weight, as well as fasting blood glucose (FBG) and lipid levels in db/db mice. Additionally, it improved renal function and effectively alleviated renal injury. Moreover, BPS decreased the expression of extracellular matrix (ECM) proteins and inhibited ECM deposition, thereby alleviating the progression of renal fibrosis in DN and reducing cell apoptosis. Notably, BPS effectively inhibited the activity of NLRP3 inflammasome in the renal tissue of db/db mice, which in turn mitigated renal inflammatory response and fibrosis.ConclusionBPS can improve renal injury and renal fibrosis in db/db diabetic nephropathy mice, which may be related to the decrease of apoptosis, inhibition of inflammation, reduction of ECM, and regulation of NLRP3 inflammasome. This study provides a scientific basis for the clinical application of BPS in the treatment of renal fibrosis in DN and is expected to promote the drug development and clinical application of BPS.